TEKEL RESISTANCE AS AN ANTI-POVERTY MOVEMENT - Şenol SIRMA (Fırat University, 2021)
The last forty years since the 1980s have witnessed intense attacks of the capital in all areas. Unfortunately, working life and employees in this context were seriously affected by these attacks. These attacks have increasingly condemned workers to precarious labor regimes. Precarization, expropriation and, finally, impoverishment in the world of work were the main apparent consequences of these attacks. This process, which means the liquidation of the public sphere, also meant deregulation in working life. The commercialization of the public sphere and the transfer of public resources to the market and other non-market actors were among the salient features of this process. The 78-day period, starting on December 15, 2009 and ending March 2, 2010, was an open opposition to the above-mentioned attacks. In the cold and snowy days of Ankara, Tekel Workers managed to be the only agenda of almost the whole country against their social rights plundered through Privatization. The view that this struggle against marketization and precarization mentioned above is an anti-poverty movement at the same time forms the basis of this study. As a matter of fact, this struggle experience of Tekel Workers is just one of many examples that can be considered as anti-poverty. The Monopoly Resistance, which will be considered as an anti-poverty movement, is also an anti-poverty movement because it is a struggle of the working class, which has become impoverished as a result of neo-liberal policies, against poverty.